Vasorelaxant effects of the extracts and some flavonoids from the buds of Coreopsis tinctoria. (September 2013) - Sun, Yu-Hua; Zhao, Jun; Jin, Hong-Tao; Cao, Yan; Ming, Ting; Zhang, Lan-Lan; Hu, Meng-Ying; Hamlati, Hasimu; Pang, Shi-Bin; Ma, Xue-Ping
Abstract Context: The buds of Coreopsis tinctoria Nutt (Compositae) are used in the treatment of hypertension in the Uyghur folk medicine in China. Objective: To investigate vasorelaxant properties of extracts and some flavonoids from C. tinctoria (CT) and their underlying mechanisms in isolated rat thoracic aortic rings. Materials and methods: Vasorelaxant effects of ethanol extracts of CT (CTA) and its flavonoids as well as water–ethanol eluates from CTA by AB-8 resins (CTAA∼CTAF) were evaluated on rat aortic rings pre-contracted with phenylephrine (PE, 1 µM) or high KCl (60 µM). We evaluated the effect of CTA, CTAD and CTAE on PE-induced contraction in a Ca2+-free medium and a dose–effect curve of Ca2+ in pre-contracted ring with high KCl. Results: Endothelial removal did not modify the effect of CTAD and CTAE (3.00 g/L) neither on PE-pre-contracted rings (164.78 ± 21.44 and 191.47 ± 16.75%) nor on KCl-pre-contracted rings (75.68 ± 10.76 and 125.14 ± 17.41%) compared with intact-endothelium rings pre-contracted with high KCl (100.49 ± 17.30 and 110.81 ± 16.33%). CTAD and CTAE (3.00 g/L) down-regulated the dose–effect curve of Ca2+ in pre-contraction with high KCl, and inhibited the pre-contraction with PE in a Ca2+-free medium (p < 0.05). Seven flavonoids were obtained from CTAD, of which luteolin (5) and quercetin (6) were found to be the most effective relaxation in rings precontracted with PE (EC50: 0.006 and 0.039 g/L, p < 0.05) or high KCl (EC50: 0.023 and 0.045 g/L, p < 0.05). Discussion and conclusion: These data demonstrated the vasorelaxant effect of CT, and its mechanism is likely due to an inhibitory effect on calcium movements through cell membranes.